Palavra mínima em português europeu: a oralização de abreviações = The minimal word in european portuguese: the oralization of abreviated forms - Veloso, João (2017)
The phonological constraints that define which phonetic chains are eligible to become a word in a given language generally include a Minimality Condition (MC). MC imposes a minimal amount of phonological substance that must be included by any single word of the language. Traditionally, MC is measured in terms of syllable weight or syllabic extension of the word. It has been much debated whether MC corresponds to a truly universal constraint; as for Portuguese, previous studies have been conflicting between the acceptance and the refusal of its productivity in the phonology of the language. In this study, we will assess the functionality of MC for the building of Portuguese lexical entries by means of observing the oralization of abbreviations. This is assumed here as a word-productive process in Portuguese. Based upon an experimental study with a group of native speakers of Contemporary European Portuguese (CEP), we conclude that (i) MC is an operative constraint in the phonology of Portuguese, and (ii) its defining criterion is purely linear and segmental. According to our proposal, MC is respected in CEP when a phonetic chain contains a minimum of three segments, regardless of syllable weight and syllabic extension.